2019
DOI: 10.1371/journal.pone.0214650
|View full text |Cite
|
Sign up to set email alerts
|

Temporal, spatial and household dynamics of Typhoid fever in Kasese district, Uganda

Abstract: Typhoid fever affects 21 million people globally, 1% of whom succumb to the disease. The social, economic and public health consequences of this disease disproportionately affect people in Africa and Asia. In order to design context specific prevention strategies, we need to holistically characterise outbreaks in these settings. In this study, we used retrospective data (2013–2016) at national and district level to characterise temporal and spatial dynamics of Typhoid fever outbreaks using time series and spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…As research generally associates environmental conditions with typhoid disease (Walters et al, 2014;Gu et al, 2017;Mirembe et al, 2019), we explored its association with the average rainfall during the study period. It was observed that the number of typhoid cases always started to raise during the rainy season of March to May, when some places with poor drainage and risk of flooding created conducive environments for bacterial survival and growth.…”
Section: Trends Of Typhoid Disease Incidence In Relation To Rainfallmentioning
confidence: 99%
See 3 more Smart Citations
“…As research generally associates environmental conditions with typhoid disease (Walters et al, 2014;Gu et al, 2017;Mirembe et al, 2019), we explored its association with the average rainfall during the study period. It was observed that the number of typhoid cases always started to raise during the rainy season of March to May, when some places with poor drainage and risk of flooding created conducive environments for bacterial survival and growth.…”
Section: Trends Of Typhoid Disease Incidence In Relation To Rainfallmentioning
confidence: 99%
“…In Uganda, over 80% of the districts are endemic for typhoid with those in the central and western regions topping the list (Agwu, 2012;Walters, et al, 2014), making Uganda only second to Nigeria in Africa with respect to typhoid (Jong-Hoon, 2017). New cases continue to be registered every day in many hospitals and clinics, and outbreaks are reported in different parts of the country (Kabwama et al, 2015;Mirembe et al, 2019). The disease is caused by a Gramnegative bacterium called Salmonella enterica serovar typhi, whose main route into the body is with drinking unsafe water or eating contaminated food as a result of poor sanitation and hygiene (Tiwari and Nayak, 2017;Mirembe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incidence varies geographically with >90% of cases in south and southeast Asia and sub-Saharan Africa, where access to water, sanitation and hygiene (WASH) infrastructure is limited [2,3]. Typhoid is especially prevalent in urban, low socio-economic settings where overcrowding and unhygienic living conditions are common [4,5]. Incidence is typically lower in rural areas, although recent findings in rural or peri-urban sites describe a higher burden than previously appreciated [6,7].…”
Section: Introductionmentioning
confidence: 99%